Motion control of a two-axis linear motor-driven stage in the micro-milling process - Heydarzadeh, Mohammad S.; Rezaei, Seyed Mehdi; Mardi, Noor Azizi; Kamali E., Ali (SAGE Publications, 2018)
The application of linear motor-driven stages as the feed drivers of CNC micro milling machine tools is growing. In addition to employ high speed and high precision equipment such as linear motor-driven stages, the precision of the machined contours is highly dependent on the capabilities of the servo controllers. In this paper, the design of a precise controller for a two-axis LMDS has been investigated for micro-milling applications. In such feed drives, disturbances such as friction, force ripples, and machining forces have adverse effects on the workpiece positioning precision due to the direct drive concept behind them. Therefore, in order to have an acceptable transient response and disturbance rejection properties, a two-degree-of-freedom proportional–integral–derivative controller was employed for each axis. To design this controller, the zero-placement method was used. To compensate disturbances and machining contour errors, the utilization of Kalman filter observers, neural networks, cross-coupled controllers, and different integration of them were studied. The controllers were experimentally examined for circular motions. An integrated controller consisted of a Kalman filter disturbance observer, a cross-coupled controller, and a well-designed two-degree-of-freedom proportional–integral–derivative controller resulted in a high contouring and tracking precision. The controller could also reduce the spikes caused by the friction at the motion reversal points such as the quadrants in circle trajectories.